Pengembangan Produk Cinderamata dari Sisa Potongan Kayu Dan Kain Tenun sebagai Upaya Pemulihan Perekonomian Pasca Pandemi di Pasar Inpres Kota Balikpapan - Eko Agung Syaputra; Olivia Febrianty Ngabito; Sasferi Yendra (Unri Conference Series: Community Engagement, 2021)
The Covid-19 pandemic has impacted traders and craftsmen at the Inpres Market Vegetable Garden, West Balikpapan Regency, experiencing difficulties in obtaining and producing their merchandise. As one of the largest islands in Indonesia, Kalimantan stores various types of wood-producing plants, especially wood from tropical forests. In the process of harvesting wood, it produces small pieces of residue that are underutilized. In addition, most of the products sold at the Inpres Market are woven fabrics with typical Kalimantan motifs. With these resources, of course, it is highly expected to be developed as a typical regional product. The purpose of this activity is to ignite diversity and improve the quality of souvenir products produced by the people of the Inpres Market area, through a social entrepreneurship approach based on the capabilities and resources of the region. Assistance activities for creative product development with a combination of wood pieces and woven fabrics are needed to initiate independent communities in the pandemic era through knowledge and skills in producing superior products from waste materials. To achieve these objectives, the methods of preparation, implementation and evaluation are used. With community service in the form of training in making creative products, traders and craftsmen in the Pasar Inpres area are able to increase independence in producing superior products that can rebuild people's income during the pandemic.